The Scientist as Philosopher Philosophical Consequences of Great Scientific Discoveries - Weinert, Friedel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
How do major scientific discoveries reshape their originators$1 (B, and our own, sense of reality and concept of the physical world? The Scientist as Philosopher explores the interaction between physics and philosophy. Clearly written and well illustrated, the book first places the scientist-philosophers in the limelight as we learn how their great scientific discoveries forced them to reconsider the time-honored notions with which science had described the natural world. Then, the book explains that what we understand by nature and science have undergone fundamental conceptual changes as a result of the discoveries of electromagnetism, thermodynamics and atomic structure. Even more dramatically, the quantum theory and special theory of relativity questioned traditional assumptions about causation and the passage of time. The author concludes that the dance between science and philosophy is an evolutionary process, which will keep them forever entwined.s
The Philosopher Scientist -- The Concept of Nature -- Physical Understanding -- The Scientist Philosopher -- The Block Universe -- Causation and Determinism -- Conclusion.
Keywords: Physics; Science; Philosophy; Popular works; Physics; Physics, general; Science, general; Philosophy, general; Popular Science, general; Electronic books